Sistemas de informações gerenciais: uma ferramenta no auxílio à gestão pública : o caso da Controladoria do Município do Rio de Janeiro - Mizurine, Marcos (2000)
What moves us!!! In the days today, it is fundamental that the public organizations are positioned in the vanguard of the technology for they face the demand, more and more growing, of the population. The atmosphere in that lived he/shelit characterizes for being highly dynamic. To every day, the constant change processes present us new problems, new responsibilities. This work has as intended to explore a delicate theme for the public organizations: the managerial information. One of the problems of the public administration is exactly the immense amount of information that he/she/it can do available to an administrator. The great subject is as to select and to organize, inside ofthat readiness, those information really usefuI. The subject 'Processo Decisório' is very including and, the focus ofthe need ofinformation was also discussed already thoroughly. However, this dissertation intends to observe the managerial information and the systems of information for another prism, that will be inside it of the insert of these tools of the government spheres, as support to the taking of decision and the transparency of the public administration. This focus stands out the importance and it demonstrates the viability of implanting systems of managerial information. The theme had as analysis object, the System of Managerial Information ofGeneral Controladoria ofthe Municipal district ofRio de Janeiro.